WOMEN, PEACE AND SECURITY – ADVOCACY AND IMPLEMENTATION OF UN RESOLUTION 1325 - Dr. Girija K.S., (IJRDO - Journal of Social Science and Humanities Research, 2023)
“Where women are full participants of politics or economy, societies are more likely to succeed – former US President Obama” The recent war by Russia on Ukraine has thrown up many issues to the forefront and peace and security occupying an important place. The devastations and the human loss that has incurred are unimaginable and horrific for women. Though threats of war was seen in many circumstances, it was not possible due to the former Soviet Union’s position and stand post world war II. However, it is unfortunate that in the present case, it’s the Russian Imperialistic tendency that has led to the war. In this context, it becomes vital to consider the UNSCR 1325 which advocates both war’s adverse effects in general and women in particular and women’s important contributions to peace and security. Yet, despite this resolution being passed women are underrepresented in the peace building process and negotiations worldwide. This article examines the role of women in peace and security process both in conflict situations and post conflict reconciliation as described in UNSCR 1325.